Konsep Beauty Privilege Membentuk Kekerasan Simbolik - Shinta Aprilianty; Siti Komariah; Mirna Nur Alia Abdullah (Ideas Publishing, 2023)
This research was conducted starting from the majority of Twitter users who expressed their disquiet about beauty privilege or special treatment for someone who was considered